Mechanism of soil breaking and prediction of pile diameter in silty clay by jet grouting using CFD-DEM coupling - Yiliang Yu; Hanlong Liu; Changbing Qin; Mingke Lin; Zhixiong Chen; Xuanming Ding (Computers and Geotechnics, 2026)

Seismic response of ultra-deep strata with weak interlayer reinforced by vertical rodin jet pile and dynamic compaction - Yiliang Yu; Hanlong Liu; Changbing Qin; Mingke Lin; Zhixiong Chen; Xuanming Ding (Engineering Geology, 2026)

Analytical framework for lateral bearing capacity of two-pile near clay slope: Group and slope effects - Changbing Qin; Mingke Lin; Yuhan Luo; Chunyan Wang; Jiangtao Yi (Ocean Engineering, 2026)

Near-infrared photobiomodulation can alleviate chemotherapy-induced peripheral neuropathy-associated sensory abnormalities - Zejun Ren; Hengtong Fan; Yuhang Chen; Mingke Chang; Shiqiu Jiang; Guoxiong Liu; Yashou Guo; Zhongyu Wang; Lijiang Gu; Dalin He; Lin Yang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Assessment of lateral capacity of semi-rigid monopile for offshore wind turbines in marine clay - Mingke Lin; Changbing Qin; Jiangtao Yi; Yiliang Yu; Xuanming Ding (Ocean Engineering, 2026)

Interface-engineered LuOx/Cu₃(HHTP)₂ heterojunction with MoO₃ interlayer for high-performance artificial optoelectronic synapses and in-sensor computing - Yutao Xiong; Zhengdong Jiang; Peicheng Jiao; Mingke Yu; Xiang Zhang; Hong Wang; Zhiqun Lin; Mengye Wang; Yanghui Liu (Chemical Engineering Journal, 2026)

Effects of scour on the bearing capacity of flexible pile in clay: An analytical approach - Mingke Lin; Changbing Qin; Xiaoqin Lei; Xuanming Ding (Ocean Engineering, 2025)

Analytical method for laterally loaded offshore slender piles near sandy slopes considering slope deformation - Chong Jiang; Maolin Sun; Pan Liu; Mingke Lin; Jing Liu (Marine Georesources & Geotechnology, 2025)

Ultimate lateral bearing capacity of rigid pile in clay considering soil stress history and scour-hole dimension - Mingke Lin; Changbing Qin; Siyu Li; Jiangtao Yi (Computers and Geotechnics, 2025)

Analysis for the effect of scour on pile lateral behavior in sand under combined loads considering additional stress and coupling effect of lateral-vertical load - Mingke Lin; Chong Jiang (Computers and Geotechnics, 2024)

Analysis of lateral bearing mechanism for offshore monopiles in sand and development of an analytical method - Pan Liu; Chong Jiang; Mingke Lin; Maolin Sun; Fanhuan Zeng (Ocean Engineering, 2024)

Study on calculation method of lateral characteristics of offshore pile near layered soil slope - Chong Jiang; Mingke Lin; Pan Liu (Ocean Engineering, 2023)

Multi-trait analysis reveals large interspecific differences for phytoplankton in response to thermal change - Mengcheng Ye; Mengting Xiao; Shufei Zhang; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Jingyuan Zhao; Xiaoying Dai; Leyao Xu; Mingke Li; Yunyue Zhou; et al. (Marine Environmental Research, 2023)

Long-term adaptation to elevated temperature but not CO2 alleviates the negative effects of ultraviolet-B radiation in a marine diatom - Peng Jin; Jiaofeng Wan; Xiaoying Dai; Yunyue Zhou; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Mengting Xiao; Jingyuan Zhao; Leyao Xu; Mingke Li; et al. (Marine Environmental Research, 2023)

Study Method of Pile near Cohesionless Slope under Reversed Lateral Load Considering Sand Strength State and Lateral Deflection of Pile - Chong Jiang; Jing Liu; Mingke Lin (Journal of Marine Science and Engineering, 2023)
A p-y curve method of pile near cohesionless soil slope under reversed lateral load is proposed. This method takes into account the failure mode of soil around the pile under reversed lateral load and the interaction mode between pile and soil, and derives the ultimate soil resistance of the pile. Considering the change of the original stress state of soil due to the lateral deflection of the pile foundation, the influence of the relative density, the initial mean effective stress and the lateral deflection of pile foundation on the internal friction angle of the sand is evaluated to further accurately calculate the soil resistance value at each depth. The prediction results of this method are well verified by comparing with the FE results and centrifuge test results. Finally, the influence of the process of lateral deflection of pile on the strength state of soil around the pile and the bearing capacity of pile is studied.